Young Lynda Carter as Wonder Woman, and Walter J. Ong’s Thought - Farrell, Thomas J. (New Explorations, 2024)
In the first part of my article, I discuss the beautiful young Lynda Carter (born in 1951) who played Wonder Woman in the Wonder Woman television series (1976-1979). As I watched the beautiful young Lynda Carter in her wonderfully revealing Wonder Woman costume, I responded to her beauty by projecting the optimal and positive form of the feminine Lover archetype in my psyche onto her, thereby making her beauty appear more attractive to me. In the second part of my article, I discuss the work of the American Jesuit Renaissance specialist and cultural historian and pioneering media ecology theorist Walter J. Ong (1912-2003; Ph.D. in English, Harvard University, 1955) of Saint Louis. Also in the second part of my article, I discuss two books by the Jungian psychoanalyst Erich Neumann (1954, 1955) and five books about the masculine archetypes of maturity by Robert Moore and Douglas Gillette (1990, 1992,1993). In the final part of my article, I return to the beautiful young Lynda Carter as Wonder Woman to offer my final reflections about Wonder Woman as a superheroine.